Desenvolvimento sustentável perene como base de elaboração e fomento das políticas públicas - um estudo de caso no município de São Sebastião - SP - Garbin, Rogério (2023)
Sustainable development has become one of the most important and urgent issues nowadays to consider that over the years the population increases and the resources necessary for the municipalities to survive exponentially decrease, thus causing a social and generational abyss. The aggravation of the problem is due to the low understanding by public managers of what sustainable development is, which, consequently, has been decisive for the excess of ineffective initiatives, when it comes to actions that are sustainable, perennial and constant in the scope of the municipalities. In this sense, each individual, family nucleus and community must be aware of what sustainable development is within their socio-economic-social context and apply it to their day-to-day activities in the city where they live. In addition to addressing the conceptual issue of sustainable development, through the case study of the municipality of São SebastiãoSP, we analyzed municipal data through documents and sustainable development reports prepared in partnership by PNUD, Petrobrás, the municipal government, as well as society. organized civil society and we demonstrate that the public policies promoted in the period are ineffective in terms of promoting perennial sustainability and we propose learning as a fundamental tool for the formation of a sustainable culture and the strengthening of a generation that is more aware of its role in reducing the abyss social and economic between generations, as well as the conscious use of currently available resources.